Light from silicon [LED]. - Coffa, S. (IEEE spectrum)
This paper discusses the current efforts to develop an electrically powered silicon laser for the fabrication of light emitting diodes (LED). Researchers have been pushing two strategies in their quest to get light out of silicon. One scheme is based on a curious effect called quantum confinement, which reduces silicon's momentum problem and increases the probability that injected electrons will produce photons. The other scheme sidesteps silicon's bandgap problems by having another material, embedded within the silicon device, emit the light. This paper proposes a combination of both techniques to produce light emitters that operate at room temperature with a controllable tradeoff between high efficiency and long lifetime. A key advantage of this approach is that the color of the light emitted depends on the rare-earth ions used. Unfortunately, this approach produces low light output because the maximum output power is limited by how densely the device can be packed with rare-earth ions. Nevertheless, researchers are confident that, within a few years, an electrically driven silicon laser will become a reality.